Design and fabrication of a mini dishwasher / Muhammad Zikry Saifullah and Nur Aini Sabrin Manssor - Saifullah, Muhammad Zikry; Manssor, Nur Aini Sabrin (School of Mechanical Engineering, 2023)
Dishwashing is a common chore in almost every household. However, this activity will take a lot of time, water, and energy to be completed. Hot water may also help make cleaning dishes much easier and give a cleaner result, but it is also dangerous to handle. Because of that, most people will resort to buying a dishwasher as it is faster and can handle the hot water. Even so, the dishwasher in the market is expensive because of its complexity and large size. Thus, this project aims to cut those costs while also providing a clean, effective, and fast dishwashing process. This could be achieved by creating a machine with basic function that is enough to get those results from the process using affordable material and components. As a result, the machine will be a great addition to a household with a low cost to be bought with a lower cost.